Human Capital Convergence and Regional Disparities: The Case of China - Yang, Jie (Université d'Ottawa | University of Ottawa, 2008)
Based on an open-economy neoclassical growth model of Barro et al. (1995), this paper examines the regional convergence of per capita GDP and various indicators of human capital stock, and the role of human capital accumulation in economic growth across 2